1993
DOI: 10.1111/j.1600-0560.1993.tb00666.x
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein in aggressive and non‐aggressive basal cell carcinoma

Abstract: Basal cell carcinoma (BCC) is the most frequent cutaneous neoplasm, with a generally favorable clinical behavior. Sometimes, indeed, it recurs after therapy and/or metastasizes. As point mutations in the coding sequence of the p53 tumor suppressor gene have been implicated in the progression of many human tumors, we studied the expression of p53 protein on this neoplasia. We tested immunohistochemically the positivity for p53 protein (NCL-p53-CM1, YLEM) on 19 cases of morphologically "non aggressive" BCC (BCC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
4
29
0
Order By: Relevance
“…This is consistent with the report of Barrett et al, 12 who found that p53 expression was highest in the aggressive subtypes and correlated with the expression of PCNA, a marker of proliferation. Similarly, overexpression of p53 was found by De Rosa et al 26 to be correlated with a more aggressive clinicopathological behavior of BCCs.…”
Section: Commentmentioning
confidence: 88%
“…This is consistent with the report of Barrett et al, 12 who found that p53 expression was highest in the aggressive subtypes and correlated with the expression of PCNA, a marker of proliferation. Similarly, overexpression of p53 was found by De Rosa et al 26 to be correlated with a more aggressive clinicopathological behavior of BCCs.…”
Section: Commentmentioning
confidence: 88%
“…78,85,86 Mutations of p53 have been documented in up to 40% of studied BCCs; 77 72% of the mutations bear the signature of UV light induction. The aggressive growth variants of sporadic BCC are associated with stromal fibroplasia and overexpression of what is likely mutant p53.…”
Section: Uv Light-induced Mutagenesis and Biologic Transformationmentioning
confidence: 99%
“…in aK patients, p53 expression extensity and CoX-2 expression intensity increased with patient age (p=0.006, p=0.004). in aK cases there was also a weak correlation between tumor size and in BCC cases (17,18). However, Healy et al did not find a significant difference between the two groups (19).…”
Section: Discussionmentioning
confidence: 96%